miRNAs and Leukotrienes in Respiratory Syncytial Virus Infection - Liu, Zhi; Fan, Panpan; Chen, Ming; Xu, Yueshi; Zhao, Dongchi (Frontiers in Pediatrics, 2021)
MicroRNAs (miRNAs) are small, noncoding RNAs that regulate post-transcription by binding to 3′-untranslated regions of target mRNAs. Recent functional studies have elucidated mechanisms that miRNAs regulate leukotriene synthesis by perturbing arachidonic acid metabolism. Both microarrays and high-throughput sequencing revealed distinct differential expression of miRNAs in children with respiratory syncytial virus (RSV) infection compared with healthy controls. Abnormal miRNA expression may contribute to higher leukotriene levels, which is associated with airway hyper-reactivity. Targeting miRNAs may benefit to restore the homeostasis of inflammatory reaction and provide new strategies to alleviate airway hyper-reactivity induced by RSV. In this article, we provide an overview of the current knowledge about miRNAs modulating leukotrienes through regulation of arachidonic acid metabolism with a special focus on miRNAs aberrantly expressed in children with RSV infection.